Sodium fluoride‐rich solid electrolyte interphase for sodium–metal and sodium–oxygen batteries. (26th August 2021) - Kim, Sujung; Jung, Younguk; Park, Jiwon; Hong, Misun; Byon, Hye Ryung
Abstract: We studied solid electrolyte interphase (SEI) on metallic sodium (Na) electrodes. Among sodium hexafluorophosphate (NaPF6 ), sodium triflate (NaOTf), and sodium bis(trifluoromethanesulfonyl)imide (NaTFSI) electrolytes, sodium fluoride (NaF)‐rich and compact SEI was only formed by chemical reduction of NaPF6 . Excellent rigidity and insolubility of NaF‐rich SEI layer enhanced electrochemical cycling performances for both Na/Na symmetric cells and sodium–oxygen (Na–O2 ) cells. By contrast, the Na electrodes using NaOTf and NaTFSI formed porous and carbonaceous SEI layers rather than NaF. Soluble carbonaceous species were detached from the Na electrode, which led to the undesired decomposition of electrolyte solution. It resulted in the substantial formation of the dead Na and dendritic Na and caused cycling failure of Na–O2 cells within 10 cycles, demonstrated by NaOTf. Abstract : Studies of solid electrolyte interface of Na metals and their effects for Na/Na nad Na–O2 cell performances.